2016
DOI: 10.4209/aaqr.2016.01.0045
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Reduction and Emission Behaviors of CBzs and PCDD/Fs from Cement Plants

Abstract: The formation, reduction and emission behaviours of chlorobenzenes (CBzs) and polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) were studied in a typical dry cement kiln in China. The operating conditions were scrutinized at various positions by monitoring the concentrations of CO, NO x , HF and HCl in the flue gas. Furthermore, the concentration, gas/particle partition and congener distribution of CBzs and PCDD/Fs were analyzed at the outlet of cyclone pre-heater, suspension pre-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Studies have shown that the formation of secondary aerosols depends on their saturation ratio and environmental conditions . Moreover, aerosols in the ambient air can be removed from the atmosphere by dry or wet deposition (Cheruiyot et al, 2015;Cheruiyot et al, 2016;Li et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the formation of secondary aerosols depends on their saturation ratio and environmental conditions . Moreover, aerosols in the ambient air can be removed from the atmosphere by dry or wet deposition (Cheruiyot et al, 2015;Cheruiyot et al, 2016;Li et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 50.1 million tons of municipal solid waste was incinerated in China in 2013 (a 33% increase over the last decade) (Han et al, 2016a;Meng et al, 2016), becoming an important emission source of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) (Xu et al, 2009;Li et al, 2012;Li et al, 2016), as well as dioxin-like compounds such as polychlorinated biphenyls (PCBs) (Guo et al, 2014). Concentrations of PCDD/Fs and PCBs released in flue gases from MSWIs primarily increase with increasing incineration temperature, and are typically adsorbed onto atmospheric particles (Cetin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the actual contribution the PCDD/Fs desorbed from KD1 made to the total emissions would be lower than the calculated value of 74 pg I-TEQ Nm À3 due to the presence of alkaline raw materials, which can inhibit the formation of PCDD/Fs in the kiln dust. 33 Moreover, gaseous PCDD/Fs will be abated when passing through the suspension preheater, raw mill, and bag lter as described by Li et al, 29 who reported a reduction in the PCDD/Fs concentration from 101 to 13 pg I-TEQ Nm À3 . Therefore, as reported by Li et al, 29 PCDD/Fs originating from their desorption from kiln dust would make a minor contribution to the overall emissions of PCDD/Fs if the PCDD/Fs reduction efficiency of 87% was achieved.…”
Section: Homologue Distribution Of Pcdd/fsmentioning
confidence: 99%
“…27 A higher mass of PCDDs in the gas phase in comparison to the mass of PCDFs indicated that precursor synthesis had occurred. 28 Previous ndings by Li et al 29 also demonstrated an abundance of precursors such as chlorobenzenes (CBzs) and polycyclic aromatic hydrocarbons (PAHs).…”
Section: Homologue Distribution Of Pcdd/fsmentioning
confidence: 99%
See 1 more Smart Citation